Differential carbon source utilization drives metabolic state and resuscitation in antibiotic-tolerant persister cells - Sun, Yufei; Roy, Sweta; Yang, Qingbo; Tang, Yinjie J.; Ren, Dacheng (Frontiers in Pharmacology, 2025)
IntroductionPersistent infections remain challenging due to dormant bacterial cells that tolerate conventional antibiotics. Specifically, persister cells, phenotypic variants characterized by high antibiotic tolerance, can resume growth once antibiotic stress is alleviated. While general metabolic traits of persister cells have been documented, the metabolic shifts during persistence and resuscitation remain poorly understood.MethodsWe applied stable isotope labeling using 13C-glucose and 13C-acetate to investigate metabolism in Escherichia coli persisters induced by carbonyl cyanide m-chlorophenyl hydrazone (CCCP). Labeling incorporation into metabolic intermediates and proteinogenic amino acids was measured using LC-MS and GC-MS.ResultsThe results demonstrated major differences in metabolic activities between normal and persister cells. Compared to normal cells, persister cells exhibited reduced metabolism. Peripheral pathways including parts of the central pathway, the pentose phosphate pathway, and the tricarboxylic acid (TCA) cycle, exhibited delayed labeling dynamics in persister cells. Proteinogenic amino acid profiling further demonstrated generalized but reduced labeling in persisters when using glucose as the sole carbon source, indicating a uniform slowdown in protein synthesis. Under acetate conditions, persister cells exhibited a more substantial metabolic shutdown, with markedly reduced labeling across nearly all pathway intermediates and amino acids. This reduction is likely due to substrate inhibition coupled with ATP demands required to activate acetate for central metabolism.DiscussionThese findings help improve the understanding of bacterial persistence by demonstrating that persister cell metabolism adapts to available carbon sources. These insights into persister metabolism may inform the development of targeted strategies to more effectively combat persistent bacterial infections.